Challenges in making standardisation work in healthcare: lessons from a qualitative interview study of a line-labelling policy in a UK region. Issue 11 (27th November 2019) - Kriznik, Natasha Marie; Lamé, Guillaume; Dixon-Woods, Mary
Abstract : Objective: To identify and learn from efforts to design and implement a standardised policy for labelling of invasive tubing and lines across a regional health system. Design: Single case study involving qualitative interviews and documentary analysis. Setting: A devolved health system in the UK National Health Service (NHS). Participants: NHS staff (n=10) and policy-makers (n=8) who were involved in the design and/or implementation of the standardised policy. Results: Though standardising labelling of invasive tubing and lines was initially seen as a common-sense technical change, challenges during the process of developing and implementing the policy were multiple and sociotechnical in nature. Major challenges related to defining the problem and the solution, limited sustained engagement with stakeholders and users, prototyping/piloting of the solution, and planning for implementation. Some frontline staff remained unconvinced of the need for or value of the policy, since they either did not believe that there was a problem or did not agree that standardised labelling was the right solution. Mundane practical issues such authorisation and resourcing, supply chains for labels, the need to restructure work practices to accommodate the new standard, and the physical features of the labels in specific clinical settings all had important impacts. Conclusions: Newly standardised tools and practices have to fit within a system of pre-existing norms, practices and procedures. We identified a number of practical, social and cultural challenges when designing and implementing a standardised policy in a regional healthcare system. Taking account of both sociocultural and technical aspects of standardisation, combined with systems thinking, could lead to more effective implementation and increase acceptability and usability of new standards.